Ultrasound assisted thermal inactivation of spores in foods: Pathogenic and spoilage bacteria, molds and yeasts - Evelyn (2021)
Background: Pasteurization aims to achieve the reduction of vegetative microorganisms and resistant spores which are of risk to public health. Power ultrasound has been identified as a potential technology for non-thermal food pasteurization. It relies on the propagation of pressure waves (frequency ranging from 20 to 100 kHz) of high intensity sound/acoustic energy (10–1000 W/cm2) inside a liquid or semisolid food, causing inactivation of pathogenic and spoilage microorganisms. This technology can also be used in simultaneous combination with temperature >80 ◦C (thermosonication, TS) to inactivate microbial spores. Scope and approach: The current knowledge on the effect of ultrasound alone (US), TS, and ultrasound followed by a thermal process (US→T) on different type of spores relevant for low- and high-acidic foods was reviewed, including the kinetic models describing their inactivation in specific foods. Key findings and conclusions: US at room temperature (without heat) has no effect on microbial spores. In terms of microbial spore inactivation efficiency, TS was the best method, followed by US→T (non-simultaneous application) and finally heat treatment without US (T). TS employing temperatures between 90 ◦C and <100 ◦C is required for spore inactivation, as at the boiling point of water ultrasound intensity is reduced. There is a need to design efficient ultrasound probes which can withstand higher temperatures or incorporate pressure to improve gas bubble implosion, thus more results can be produced at higher temperatures and with different type of microorganisms. When reporting results from TS experiments, standardized ultrasound processing conditions including the actual power delivered to the food and expressed in acoustic power density (power/volume of liquid food, W/mL) or specific acoustic power (W/g food) should be used to allow the comparison of results from different studies. TS inactivation kinetics of some spores of bacteria and molds exhibited non-linear trends, thus TS should be examined in detail for reliable food processing